2008
DOI: 10.1515/cclm.2008.099
|View full text |Cite
|
Sign up to set email alerts
|

Down's syndrome screening: population statistic dependency of screening performance

Abstract: The Access triple test meets the typical performance characteristics for this test combination. The assay-specific settings yielded the overall best efficacy for the criteria studied. Therefore, the availability of measurement procedure-specific mid-trimester reference values for unaffected and affected pregnancies in prenatal screening programs is essential. Such reference values are established for the Beckman Coulter Access triple test: maternal serum AFP, uE3 and hCG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The characteristics of the studies are presented in Table 1 . A total of 18 articles 10 16 17 18 19 20 23 24 25 26 27 28 29 30 31 32 33 34 with 183,998 samples were included in this meta-analysis. The sample sizes of these studies ranged from 221 to 37,362, and the average number of samples per study was 10,222.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the studies are presented in Table 1 . A total of 18 articles 10 16 17 18 19 20 23 24 25 26 27 28 29 30 31 32 33 34 with 183,998 samples were included in this meta-analysis. The sample sizes of these studies ranged from 221 to 37,362, and the average number of samples per study was 10,222.…”
Section: Resultsmentioning
confidence: 99%
“…These voluntary screening tests which are used to evaluate the risk of DS consist of measuring combinations of biomarkers in maternal serum, including alpha fetoprotein (AFP), total human chorionic gonadotropin (hCG), free beta subunit of hCG (β-hCG), unconjugated estriol (uE3), pregnancy-associated plasma protein A (PAPP-A), proform of eosinophil major basic protein (ProMBP), inhibin-A, and placental growth factor (PGF). Studies of DS-affected pregnancies have demonstrated that serum screening tests exhibit sensitivities of 70–85% and specificities of 90–96% 16 17 18 . In recent years, ultrasonographic nuchal translucency (NT) measurements during the first trimester of gestation have been used in combination with serum screening tests; the integrated screening tests yield sensitivities of 90–95% with acceptable false-positive (FP) rates 19 20 .…”
mentioning
confidence: 99%